The oil sorption behaviour investigation of kapok (Ceiba Pentandra (L.)) fiber - Daniel, M Afiq; Raja Ahmad, Raja Adibah; Hussin, R; Hamidon, M. Adam Bukhori; Harun, Z; Yunos, M Z; Ainuddin, A R (2024)
As oil exploration and production activities have risen globally, water contamination from oil spills and the discharge of other oily wastewaters has emerged as one of the primary environmental concerns. Thus, Kapok fiber is considered in this study as it is known as one of the most effective method for cleaning up and collecting oil spills where Kapok is a natural cellulosic fiber with unique characteristics. A critical investigation was conducted to study the potential of kapok fiber as sorbent material, also analyze the surface properties of kapok fiber for the ability of kapok fiber to absorb oil and investigate the sorption mechanisms of kapok fiber. Therefore, the surface properties of kapok fiber were analyzed using SEM, FTIR, TGA and contact angle. To investigate the selectivity nature and the sorption capacity of 5 g kapok fiber, different types of oil and different apparent viscosity were used. The types of oil used are gear oil (low viscosity), vegetable oil-based cooking oil (medium viscosity) and waste oil (high viscosity). Kapok fiber was able to absorb all types of oil, with wasted oil absorbing the most about 17.88 g.g-1. Scanning electron microscopy (SEM) was used to examine the morphology of raw kapok fiber. In this study, kapok fiber was shown to have a porous hollow lumen structure and a waxy coating on the surface. Other than that, for the contact angle analysis, kapok fiber had high water contact angle up to 130˚. The water droplet was stood on the kapok fibers surfaces before and after absorption with contact angles ranging from 130˚ to 145˚. In contrast, the oil droplet had disappeared from the surfaces of kapok fiber within a few seconds